Low frequency of human papillomavirus detection in prostate tissue from individuals from Northern Brazil - Silvestre,Rodrigo Vellasco Duarte (2009)
The presence of human papillomavirus (HPV) was evaluated in 65 samples of prostate tumours and six samples of prostates with benign prostatic hyperplasia from individuals from Northern Brazil. We used a highly sensitive test, the Linear Array HPV Genotyping Test, to detect 37 high and low-risk HPV types. In this study, only 3% of tumour samples showed HPV infection. Our findings support the conclusion that, despite the high incidence of HPV infection in the geographic regions studied, HPV was not associated with a higher risk of prostate cancer. To our knowledge, this is the first study evaluating the frequency of HPV detection in prostatic tissue of individuals from Brazil.